2013
DOI: 10.1111/dar.12031
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension, chronic obstructive pulmonary disease, diabetes and depression among older methadone maintenance patients in British Columbia

Abstract: Higher rates of COPD among MMT clients is likely explained by elevated smoking, and higher rates of depression may be explained by multiple disadvantages associated with substance use. Although the groups were similar for diabetes prescriptions, the MMT group likely experienced barriers to receiving treatment since prior research suggests their rates should be elevated due to methadone use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 22 publications
0
27
0
2
Order By: Relevance
“…However, like all opioids, both methadone and buprenorphine have risk of addiction and often have potential of drug-drug interactions [7] . Opioid substitutes are also linked to diabetes, nicotine addiction, and premature death [8] [10] . Therefore, there is a strong interest in finding alternative treatments for SUD.…”
Section: Introductionmentioning
confidence: 99%
“…However, like all opioids, both methadone and buprenorphine have risk of addiction and often have potential of drug-drug interactions [7] . Opioid substitutes are also linked to diabetes, nicotine addiction, and premature death [8] [10] . Therefore, there is a strong interest in finding alternative treatments for SUD.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the heterogeneity of the types of drugs used and style of intervention, it is hard to summarise meaningfully the available data of existing interventions. However, with relapse rates as high as 60% 1 year after treatment for substance use disorders (SUD) [ 10 12 ] and 60–90% for alcohol use disorders (AUD) [ 13 16 ] and drug substitution therapies being associated with innate complications [ 17 20 ], there is a need for evidence for new treatments and preventive interventions to help address the growing burden of alcohol and/or substance use.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have shown that SUD is associated with preventable conditions/ACSCs ( Sumino et al, 2014 , Sumino and Cabana, 2013 , Caponnetto et al, 2013 , Clark et al, 2009 , Gore et al, 2010 , Maruyama et al, 2013 , Coffey et al, 2012 ), the relationships between ACSC admissions and substance use/dependency are relatively under-explored. In a systematic qualitative review of studies on preventable hospitalization in chronic diseases, Muenchberger and Kendall found that over one-third of the reviewed studies focused on health status, socioeconomic status, or general demographics, whereas substance abuse/dependency was examined by less than 5% ( Muenchberger and Kendall, 2010 ).…”
Section: Introductionmentioning
confidence: 99%